Recent developments in intrinsically conductive polymer coatings for corrosion protection - Khan, M. I.; Chaudhry, Ali Usman; Hashim, S.; Zahoor, M. K.; Iqbal, M. Z. (Chemical Engineering Research Bulletin, 2010)
Intrinsically conductive polymers have achieved demanding interest in the field of corrosion control coatings owing to their conductive ability and also due to the strict environmental regulations on conventional heavy metals coatings. This multipurpose class of polymers has shown to be effective and proven themselves as a potential alternate for these hazardous heavy metal coatings in order to control the corrosion properties of metals or alloys. The basic purpose of this paper is only to highlight the past decade work relating to the efforts made on protection of metals from corrosion using conductive polymers. The categorization of the coatings is based on the techniques used to apply them. This paper will also discuss the synthesis and prospective applications of these coatings depending on their different formation techniques. Keywords: Conductive polymers; corrosion; coatings DOI = 10.3329/cerb.v14i2.5918 Chemical Engineering Research Bulletin 14 (2010) 73-86